Potion problems eaudiobook - Callaghan, Cindy (Just Add Magic, 2020)
Now an Amazon Streaming Series Kelly Quinn and her friends must figure out a way to save a beloved local store and find their infamous Secret Recipe Book , which has gone missing in this sequel to Just Add Magic . Kelly Quinn and her best friends, Darbie and Hannah, are having the worst day ever! Their Secret Recipe Book accidentally gets included in frenemy Charlotte's used book drive. Not good. As if that's not enough, the girls find out that their cooking program is on the chopping block at school, thanks to big budget cuts. Kelly & Company decide to take matters into their own hands and apply for famous TV chef Felice Foudini's Recipe Challenge. The prize? $10,000 and webisodes on Felice's site. With the Book and the special ingredients from their beloved mentor Senora Perez's store LaCucina, the girls are sure to win. But when they turn to Senora Perez, for help, they discover La Cucina is in danger of closing! Then Kelly gets a mysterious delivery—a package with the missing Secret Recipe Book with a note: "From KE." KE is one of the Book's authors, but who is KE exactly? It's up to Kelly, Darbie, and Hannah to get to the bottom of the mystery, save the cooking program, and help Senora P. keep her store!